Optimización de la gestión contable en la operatividad aduanera de la empresa Agencia de Aduana AMT SAC: 2017-2021 - Plasencia Cotrina, Edward Stevie (2022)
This report covers all my professional development as an Accounting Analyst with a time of permanence greater than 4 consecutive years in the company “Agencia de Aduana AMT SAC”; a company in the customs sector that provides the logistics service of imports and exports to various companies from Trujillo and Lima. During the development of the report, we can find information about the institutional context of the company and the description of my functions developed in the accounting area for the period already mentioned, during the application of my functions I was able to apply the knowing learned in my university stage. Among the functions he had developed are the preparation of customs settlements and invoicing to customers, the monitoring of balances by customs services, preparation of the monthly tax settlement, monitoring bank reconciliations, and reviewing the balances of accounting accounts for the preparation of monthly closings and financial statements. Finally, strategies, tools and mechanisms were established so that the problems that were found at the time can be solved so that in the future the accounting area has better control over operations; In addition, a proposal was presented to improve the curricular mesh of the Accounting and Finance School of the National University of Trujillo.